Measurement of WZ and ZZ production in pp collisions at in final states with b-tagged jets - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (Springer New York LLC, 2014)
Measurements are reported of the WZ and ZZ production cross sections in proton-proton collisions at (Formula presented.) in final states where one Z boson decays to b-tagged jets. The other gauge boson, either W or Z, is detected through its leptonic decay (either (Formula presented.)). The results are based on data corresponding to an integrated luminosity of 18.9 fb(Formula presented.) collected with the CMS detector at the Large Hadron Collider. The measured cross sections, (Formula presented.), are consistent with next-to-leading order quantum chromodynamics calculations.